THE CULTURE OF QUR’ANIC LITERACY IN PUBLIC SCHOOLS: AN ETHNOGRAPHY OF THE MORNING (TADARUS) TRADITION AND STUDENT CHARACTER BUILDING - Muhammad Agus Salim; Nia Hasanah; Uswatun Hasanah; Toib (STAI Nusantara Kota Banda Aceh, 2026)
This study is motivated by the decline in students' character and their decreasing engagement with religious values amid the rapid development of the digital era. The study aims to analyze the role of Qur'anic literacy culture through the morning tadarus (Qur'an recitation) tradition in shaping students' character in public schools. A qualitative approach with an ethnographic design was employed. Data were collected through observation and documentation involving the principal, Islamic Religious Education teachers, homeroom teachers, religious activity coordinators, and selected students using purposive sampling. Data were analyzed through the stages of data condensation, data display, and conclusion drawing. The findings reveal that the morning tadarus tradition has become a religious school culture that contributes to the development of students' religious character, discipline, responsibility, politeness, and social awareness through habituation, role modeling, and the reinforcement of Qur'anic values. The success of the program is supported by school leadership, teachers' exemplary conduct, students' participation, and family support. This study concludes that a Qur'anic literacy culture effectively strengthens character education in public schools.